BUTACHLOR INDUCED SERUM BIOCHEMICAL ANOMALIES CORRELATED WITH HISTOPATHOLOGICAL CHANGES IN INTESTINAL TISSUE OF Clarias batrachus (LINN.): In-vivo STUDY - CHAND, GYANENDRA BAHADUR; VERMA, PRAKRITI; SINGH, PRAKASH; PRASAD, SUDAY (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2021)
The present study aimed to investigate the adverse effects of butachlor (2-chloro-2', 6’-diethyl-N - butoxymethyl) acetanilide on serum total protein and glucose level and histo-pathological changes in small intestine especially proximal part (duodenum) of walking catfish Clarias batrachus (Linn.). 96 hour LC50 of butachlor for the fish was determined by the probit regression and then the experimental fishes were exposed to sub lethal dose (1.5µl/ L i.e. 1/36th of LC50) for 7, 14 and 21 days respectively. Blood samples were collected in heparinised syringe by puncturing the caudal vein and the serum was extracted as per standard protocol. The proximal part of intestine was dissected out and fixed in aqueous Bouin’s fixative. Paraffin spread sections were double stained in haemotoxylin and eosine, mounted in DPX and viewed under Olympus 2000 trinocular compound microscope. Light microphotographs were taken in canon ISUS 130X digital camera. Serum total protein and glucose estimation was done as per standard protocol. The LM study of intestinal tissues of treated fish showed degeneration in mucosa, sub-mucosa and muscularis mucosa region of duodenum in comparison to that of control fish. After 7 and 14 days exposure of butachlor the degeneration were prominent in tunica mucosa and sub mucosa layer as marked by erosion of brush borders of villi and basal lamina, hypertrophy of goblet cells, appearance of large number of vacuoles in sub mucosa region and migration of lymphoid tissues in the lamina proporia. Exposure of butachlor for longer duration of 28 days resulted in widening of luminal region, necrosis of goblet cells, roblet cells as well as entero-endocrine cells. Besides, extensive haemorrhages and congested absorptive region were prominently marked. Biochemical results of treated fish showed significant decrease in serum total protein and abnormal fluctuation in glucose level in contrast to control. A significant (p<0.05) consistent decline in serum protein can be correlated with the diminished absorption rate of protein by the altered intestinal enterocytes under butachlor stress. Hence elevated serum protein level correlated with histopathological alteration in the proximal intestine of fish may be considered as bio-indicator of polluted aquatic bodies.